Acetylcholinesterase and butyrylcholinesterase inhibitory activities of antioxidant peptides obtained from enzymatic pea protein hydrolysates and their ultrafiltration peptide fractions. Issue 11 (27th June 2022) - Asen, Nancy D.; Aluko, Rotimi E.
Abstract: This study optimized the enzymatic hydrolysis of yellow field pea proteins using alcalase (ACH), chymotrypsin (CHH), flavourzyme (FZH), pancreatin (PCH), pepsin (PEH), and trypsin (TPH) to obtain hydrolysates and ultrafiltered fractions (<1, 1–3, 3–5 and 5–10 kDa) that possess antioxidant plus acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibitory activities. The hydrolysates exhibited varying degrees of radical scavenging and inhibition of linoleic acid peroxidation, as well as cholinesterase inhibition activities but the potency generally improved by >10% after UF separation into peptide fractions. ACH, FZH, and PEH exhibited significantly ( p < .05) higher (20%–30% increases) radical scavenging activities than the other hydrolysates. The 1 and 3 kDa UF fractions of ACH, FZH, and PEH inhibited 20%–30% AChE activity, while ACH, PCH, TPH, and PEH inhibited 20%–40% BuChE activity. We conclude that the pea protein hydrolysates and their peptide fractions possess multifunctional properties with potential use against neurodegenerative disorders. Practical applications: Alzheimer's disease (AD) has multiple pathological pathways in addition to the loss of acetylcholine (ACh) catalyzed by acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). The presence of severe oxidative stress triggered by lipid peroxidation and formation of free radicals is a common trait in AD patients. The concept of AChE and BuChE inhibition as an approach toward AD amelioration involves the use of compounds with a similar structure to ACh, the natural substrate. Peptides derived from food proteins consist of ester bonds with structural similarity to ACh and theoretically possess the ability to interact with AChE and BuChE. Results from the present study imply that pea protein‐derived peptides are potential candidates for use as inhibitors of AChE and BuChE activities, with application in the prevention and management of AD. Abstract :